Intellectual property rights : the role of patents in renewable energy technology innovation (International Renewable Energy Agency, 2013)
Patent information can provide valuable insights on the renewable energy sector as new technologies arise and markets continue to evolve. Analysis of renewable energy technology patents, for example, can reveal: which countries and innovators are most active in inventing technologies; the potential markets where technologies need to be protected; technological development trends in certain fields of technology over time; trends in technology transfers from one country to another; and patterns of international research and co-operation, as indicated by co-invention and co-ownership. This book outlines how and when to use patents in order take renewable energy technologies forward.